Pengaruh Manajemen Laba, Kebijakan Dividen, dan Pertumbuhan Perusahaan terhadap Nilai Perusahaan - Irene Janice; Titik Aryati (Jurnal Riset Akuntansi, 2024)
This study aims to examine the effect of earnings management, dividend policy, and company growth on firm value. Firm value is measured by price book value (PBV). Quantitative methods are used in this study by using secondary data sources. Researchers took data on companies from 2017 to 2020 and used the analysis unit of manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange. The method of determining the sample in this study used purposive sampling. Analysis of the data used as hypothesis testing is multiple regression analysis. The results of this study indicate that earnings management and dividend policy have a positive effect on firm value, while firm growth has no effect on firm value.